Study on organic anion (BSP) transport in Analbuminemic Rat (NAR) - MURAKI, Toshio; CHIBA, Kazuo; YAMADA, Hideo; TANNO, Munehiko; NAGASE, Sumi; NAGASHIMA, Junichi (Kanzo, 1984)
To investigate of the effect of serum albumin on serum clearance of organic anion, cumulative excretion rates of BSP into bile were measured in SD rat and Analbuminemic Rat (NAR). In SD rat, 70.7±4.9% of administered dose was excreted within 15min after intravenous injection of 0.5mg BSP/100g body weight, whereas these in NAR decreased to 53.7±1.4%, respectively. Similar tendency was also observed in both group administered of 0.25mg BSP/100g body weight. However, there is no apparent effect on cumulative excretion rate of BSP in NAR, when serum albumin and BSP administered simultaneously to NAR. These results suggest that serum albumin and assumptive albumin receptors on the liver plasma membranes do not probably have a important role for the uptake of organic anions into hepatocyte.